Consequences of service quality in the insurance industry: A case study on Saudi Arabia insurance industry - Mohammed Saad, Alawni; Islam, Rabiul; Noor, Mohd Saifoul Zamzuri; Ali, Jamal; Zainal, Zalina (Medwell Journals, 2016)
This study investigated the consequences of service quality in the insurance industry and attempted to examine a well-established association between service quality, customer satisfaction and customer loyalty that has been investigated thoroughly in literature concerning the topic in different countries.Insurance service is different from other services as it is complex and future contingent service involves substantial legal characteristics.Hence, in order to succeed and survive in this environment, any economic enterprise needs to deliver quality service.This study also attempted to look into the service quality provided by the Saudi insurance industry in light of its consequences.Customers of Saudi insurance organizations will constitute the sample of the study.Therefore, this study is going to take health insurance regarding to the important of this section to investigate its role of customer loyalty.The root of the main deficiency is probably lack of knowledge which suggests the need for greater awareness of the acceptability of insurance and of its potential benefits to consumers.Health insurance in particular can be emphasized as it is also popular in industrialized nations